Specialized intensive inpatient rehabilitation is crucial and time-sensitive for functional recovery from disorders of consciousness - Zhang, Bei; O'Brien, Katherine; Woo, Jean; Chi, Bradley; Reeh, Colton; Li, Sheng; Kothari, Sunil (Frontiers in Neurology, 2023)
Background: Disorders of consciousness (DoC) is considered a dire situation after severe brain injuries. Despite the accumulating evidence, inpatient rehabilitation is often denied by payors referring to the Medicare/Medicaid criteria with the assumption that these patients wouldn’t “actively” participate or make “measurable improvements.” Objective: To report the effectiveness and efficiency of a specialized inpatient DOC rehabilitation program based on measurable clinical parameters. Methods: A retrospective cohort study comprised of 137 patients with DoC admitted to a specialized acute inpatient rehabilitation program during 1/2014-10/2018. Patient were categorized as admitted in an acute (<=28 days postinjury), subacute (29-365 days following a traumatic brain injury (TBI) or 29-90 days following a non-TBI), or chronic (>365 days following a TBI or >90 days following a non-TBI) stages. Outcomes included changes in the level of consciousness (based on Coma Recovery Scale–Revised (CRS-R); also acknowledging scenarios beyond CRS-R with Individualized Qualitative Behavioral Assessment and team consensus), Functional Independence Measure (FIM) levels, achievements in decannulation and oral diet, and time to those achievements. Results: The rates of emergence from minimally conscious state were 90%, 62%, 18% admitted in acute, subacute, chronic stages, respectively. Among the emerged patients, 100%, 85%, 67% had measurable FIM scores, respectively; around 60% and 20% in acute and subacute stages required moderate assist or less in transfer/communication/eating/grooming/upper body dressing by discharge from Phase I admission. The decannulation rates were 94%, 67%, 17%, respectively. The oral diet initiation rates were 70%, 23%, 6%, respectively. The time to reach the achievements lengthened as chronicity evolved. There was a weak positive correlation (rs = 0.308) for decannulation and a strong positive correlation (rs = 0.606, both p < 0.01) for oral diet between days since injury on admission and days to the achievement since admission. Patients with TBI and hypoxic brain injury had comparable recovery rates when admitted in acute and subacute stages. Conclusion: Specialized intensive inpatient rehabilitation is crucial and time-sensitive for functional recovery from DoC caused by TBI and hypoxic ischemic brain injury. Specific goals and different outcome measures need to be developed to appraise the benefits of acute inpatient rehabilitation for DoC.